IMPLEMENTASI METODE STORYTELLING DALAM PEMBELAJARAN SKI TERHADAP PARTISIPASI AKTIF SISWA KELAS III DI IQ SMART EDUCATION CENTER KARAWANG - Salsabila Khonsa Setiawan, Ayyomi; Dwi Basuki, Danang (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the implementation of the storytelling method in Islamic Cultural History (SKI) instruction and its impact on the active participation of third-grade students at the IQ Smart Education Center in Karawang. This study was motivated by the low level of student participation in SKI learning due to the use of conventional, teacher-centered teaching methods. The objectives of this study are to describe the process of implementing the storytelling method, the forms of active student participation, as well as the supporting and inhibiting factors during the learning process. This study employs a descriptive qualitative approach. Data collection techniques were conducted through structured interviews and documentation with third-grade SKI teachers as the primary informants. The results of the study showed that the storytelling method was able to create a more active and engaging learning atmosphere. Students participated through activities such as listening, asking questions, answering, and retelling the stories presented by the teacher. The use of simple language, vocal intonation, and the teacher’s facial expressions also helped students understand the learning material. However, several obstacles were still found, such as students easily losing focus and becoming distracted during learning. Therefore, teachers are advised to make greater use of more varied and interactive learning media to maintain student participation.